MUHAMMAD ABED AL-JABIRI, NALAR BUDAYA ARAB, DAN IMPLIKASINYA DALAM PENDIDIKAN ISLAM - Ahmad Lahmi; Sandra Ayu (Ruhama : Islamic Education Journal, 2019)
Abstract: This study was conducted on the thought of Muhammad Abed al-Jabiri, in his work "Takwim al-qAql al-Arabi" trying to build buildings, especially special Arabic cultural reasoning. From the results of the study that the author found is the reason of Arabic culture which refers to the normative of everything, which one refers to the thought to look for the position and location of something in the value system that is used as a reference and research center. In another perspective, the normative perspective is also a reductive perspective which gives rise to perspective only on aspects of values, and the consequences of the given meaning (community and culture) that uses that perspective. This is contrary to the objective (Greek-European) in discussing something by searching for a non-subjective. In other words, an objective perspective is a structural analytical perspective, analyzing something to the point of being incompatible, in order to reconstruct it, in a form that can display its substance. The relevance of the conceptions needed needs to improve the Islamic education system which prioritizes the Islamic education system in order to be able to base its knowledge style based on empiricism and research. Keywords: reason, culture/'aql, thaqaafah